Strategi Dakwah Habib Ali Zainal Abidin Al Hamid Pada Masyarakat Desa Ketapang Banyuwangi - Kholisol Hadi; Wisri (Fakultas Dakwah Universitas Ibrahimy, 2024)
This article aims to describe Habib Ali Zainal Abidin's preaching strategy to the Ketapang Banyuwangi community along with supporting and inhibiting factors. A Muslim's busy work life causes his Koran worship activities to start to be put aside and even to be largely ignored. Seeing this phenomenon, da'wah activities must be better by presenting da'wah that has a plan and can bring about change. Habib Ali Zainal Abidin was present in the Ketapang Banyuwangi community to provide a new nuance of preaching. The da'wah carried out by Habib Ali was by creating several assemblies so that they could provide direct communication in transferring knowledge to the people of Ketapang, Banyuwangi District. Study of fiqh, Sufism and accompanied by qosidah salawat and dhikr. The method used in this research is qualitative with a descriptive type, meaning research that aims to create systematic, factual and accurate descriptions, images or paintings regarding the facts, characteristics and relationships between the phenomena being investigated. The findings showed that Habib Ali Zainal Abidin's preaching to the people of Ketapang Banyuwangi provided scientific material by providing solutions, giving examples with morals, calling with sincerity, visiting the community directly, not distinguishing between classes in society, istiqomah in preaching, and using the mauidzhah hasanah method . The supporting factor for Habib Ali Zainal Abidin's da'wah is that he is a preacher who is pious in religious knowledge and has a conducive place as a means for him to preach. Meanwhile, the obstacle to his preaching was that there were some people around the Islamic boarding school who were socially jealous and misunderstood the associations they held so they did not want to join in his studies.